Energy analysis and optimization of heat integrated air separation column based on non-equilibrium stage model - Ja'afar Sulaiman Zangina; Muhammad Aliyu Suleiman; Abdulla Ahmed (Results in Engineering, 2023)
A large scale of nitrogen and oxygen production has been through a cryogenic air separation process. This process takes place in a distillation column at excessive energy consumption. The heat-integrated air separation column (HIASC) can save energy when utilizing minimum pressure while ensuring adequate heat distribution along the portion of the column. However, accurate prediction of thermodynamic and fluid properties requirement is critical for process optimization and potential energy saving. The nonequilibrium stage model is employed to gain insight into the thermodynamic properties. While examining the influence of these properties, essential process operating variables are optimized to save energy. The research result shows that more than 17% of energy is preservable in the HIASC.